Solar activity and Pacific decadal oscillation caused abnormally warming in the Khingan Mountains of Northeast China during 1876–1904 - Zhuoying Li; Changfeng Sun; Yu Liu; Xuan Wu; Mengdan Jing; Jiachuan Wang; Qiufang Cai; Meng Ren; Huiming Song; Qiang Li (Climate Dynamics, 2026)

Historical evolution and future trend of meteorological drought in the upper Yangtze River basin - Chang Yu; Wenxin Li; Cuishan Liu; Yun Wang; Ruimin He; Guoqing Wang (Climate Dynamics, 2025)

Precipitation pattern changes in Northern China before and after the weakening of the Asian summer monsoon - Xuan Wu; Changfeng Sun; Yu Liu; Huiming Song; Mengdan Jing; Zhuoying Li; Qiufang Cai; Meng Ren; Qiang Li (Climate Dynamics, 2025)

Three-dimensional structure of interannual-to-decadal variations in water temperature in the Yellow sea during 1998‒2021 - Fangguo Zhai; Bing Yu; Yujie Dong; Yanzhen Gu; Zizhou Liu; Peiliang Li (Climate Dynamics, 2025)

Continental cold-air-outbreaks under the varying stratosphere-troposphere coupling regimes during stratospheric Northern Annular Mode events - Yueyue Yu; Rongcai Ren; Yafei Li; Xueting Yu; Xuhui Yang; Bowen Liu; Ming Sun (Climate Dynamics, 2024)
A Stratospheric Northern Annular Mode (SNAM) phase-based composite analysis reveals that continental Cold Air Outbreaks (CAOs) can occur during both positive and negative SNAM events. CAOs tend to occur over Asia, characterized by a meridional-dipole surface temperature anomaly pattern (cold midlatitudes and warm high-latitudes) when the SNAM index is decreasing or the stratospheric polar vortex is weakening, but over North America and Europe with a meridionally-homogeneous pattern when the SNAM index is increasing or the stratospheric polar vortex is strengthening. While the decreasing SNAM is dominated by a stronger stratospheric poleward warm branch (WB-ST) of the isentropic meridional mass circulation and vice versa, the CAOs always follow a stronger tropospheric poleward warm branch (WB-TR) and an equatorward cold branch (CB) of the isentropic meridional mass circulation. The correspondence between the stronger/weaker WB-ST and stronger/weaker WB-TR&CB during majority of SNAM phases (referred to as stratosphere-troposphere coupling regimes) is responsible for the CAOs in Asia. During the remaining phases (stratosphere-troposphere decoupling regimes), in accompany with a weaker/stronger WB-ST, the WB-TR&CB are stronger/weaker and relates to the CAOs occurred in North America and Europe. The coupling regimes when the stratospheric polar vortex is weakening/strengthening are mainly attributed to the E-P flux convergence/divergence from the middle troposphere to the lower stratosphere, the larger wave amplitude throughout the column, and anomalous tropospheric wave flux mainly in the Asia in subpolar latitudes. The decoupling regimes, however, are mainly related to the anomalous westward-tilting of waves and the wave flux reflection toward the North America or Europe.

Correction to: Structure of the Western Tibetan Vortex inconsistent with a thermally‑direct circulation - Xiao‑Feng Li; Jingjing Yu; Shaofeng Liu; Jingzhi Wang; Lei Wang (Climate Dynamics, 2023)

Impact of the leading atmospheric wave train over Eurasia on the climate variability over the Tibetan Plateau during early spring - Yaoxian Yang; Yimin Liu; Zeyong Hu; Haipeng Yu; Jinxiao Li; Yongkun Xie; Qian Yang (Climate Dynamics, 2023)

Sensitive climate response of tree-ring δ18O to current warming in the Qinling Mountains along a climate boundary in China - Qiang Li; Yu Liu; Huiming Song; Ruoshi Liu; Qiufang Cai; Changfeng Sun; Congxi Fang; Hai Cheng (Climate Dynamics, 2023)

The linear behavior of the joint initial-boundary-value predictability of the climate system - Jianlin Yong; Shaoqing Zhang; Zhengyu Liu; Yang Gao; Lixin Wu; Jianping Li; Lv Lu; Yingjing Jiang; Xiaolin Yu; Mingkui Li; Haoran Zhao; Xiaopei Lin (Climate Dynamics, 2023)

Structure of the Western Tibetan Vortex inconsistent with a thermally-direct circulation - Xiao-Feng Li; Jingjing Yu; Shaofeng Liu; Jingzhi Wang; Lei Wang (Climate Dynamics, 2022)
The Western Tibetan Vortex (WTV) is a large-scale circulation pattern identified from year-to-year circulation variability, which was used to understand the causal mechanisms for slowdown of the glacier melting over the western Tibetan Plateau (TP). A recent argument has suggested the WTV is the set of wind field anomalies resulting from variability in near-surface air temperatures over the western TP (above 1500 m), which, in turn, is likely driven by the surface net radiation. This study thereby evaluates the above putative thermal-direct mechanism. By conducting numerical sensitivity experiments using a global atmospheric circulation model, SAMIL, we find a WTV-like structure cannot be generated from a surface thermal forcing imposed on the western TP. A thermally-direct circulation generated by the surface or near surface heating is expect to cause upward motions and a baroclinic structure above it. In contrast, downward motions and a quasi-barotropic are observed in the vertical structure of the WTV. Besides, we find variability of the surface net radiation (sum of the surface shortwave and longwave net radiation) over the western TP can be traced back to the WTV variability based on ERA5 data. The anticyclonic (cyclonic) WTV reduces (increases) the cloudiness through the anomalous downward (upward) motions, causes more (less) input shortwave net radiation and thereby more (less) surface net radiations, resulting in the warmer (cooler) surface and near-surface air temperature over the western TP. The argument is constructive in encouraging examination of the radiative balance processes that complements previous studies.

Recent intensification of hydroclimatic change in the middle reaches of the Yangtz River Basin driven by PDO, ENSO and WPSH - Qiufang Cai; Hengjun Qian; Yu Liu; Congxi Fang; Hanyu Zhang; Qiang Li; Changfeng Sun; Huiming Song; Ruoshi Liu; Junyan Sun (Climate Dynamics, 2022)

Impact of North Atlantic SST and Tibetan Plateau forcing on seasonal transition of springtime South Asian monsoon circulation - Wei Yu; Yimin Liu; Xiu-Qun Yang; Guoxiong Wu; Bian He; Jinxiao Li; Qing Bao (Climate Dynamics, 2021)
The South Asian circulation and precipitation in spring shows a clear seasonal transition and interannual variation. We investigate how the North Atlantic sea surface temperature (SST) and Tibetan Plateau (TP) forcing affect this seasonal transition over South Asia on interannual timescale. Our results suggest that North Atlantic SST can affect the seasonal transition of South Asian monsoon via TP forcing in spring. The positive tripole pattern of North Atlantic SST anomaly during winter–spring can trigger a steady downstream Rossby wave train with cyclonic circulation over the southwestern TP. This forms a spring dipole mode of surface sensible heating and 10 m winds over the plateau, with a westerly (easterly) flow and positive (negative) surface sensible heating over its southern (northern) regions. A distinct land–air coupling configuration in May is then generated on the southwestern TP via such a positive TP dipole mode, which consists of anomalous positive precipitation, negative surface sensible heating and a baroclinic circulation structure with cyclonic circulation in the mid- to upper troposphere and a shallow anticyclonic circulation in the lower layer. The anticyclonic circulation is opposite to the summertime monsoon circulation. It weakens the cross-equatorial flow and water vapor transport to the South Arabian Sea and Bay of Bengal, resulting in in-situ precipitation reduction. Consequently, the seasonal transition in circulation over South Asia from winter to summer is delayed.

Similarities and differences in driving factors of precipitation changes on the western Loess Plateau and the northeastern Tibetan Plateau at different timescales - Changfeng Sun; Yu Liu; Qiufang Cai; Qiang Li; Huiming Song; Congxi Fang; Ruoshi Liu (Climate Dynamics, 2020)

Coupled data assimilation and parameter estimation in coupled ocean–atmosphere models: a review - Shaoqing Zhang; Zhengyu Liu; Xuefeng Zhang; Xinrong Wu; Guijun Han; Yuxin Zhao; Xiaolin Yu; Chang Liu; Yun Liu; Shu Wu; Feiyu Lu; Mingkui Li; et al. (Climate Dynamics, 2020)

A new DRP-4DVar-based coupled data assimilation system for decadal predictions using a fast online localization technique - Yujun He; Bin Wang; Wenyu Huang; Shiming Xu; Yong Wang; Li Liu; Lijuan Li; Juanjuan Liu; Yongqiang Yu; Yanluan Lin; Xiaomeng Huang; Yiran Peng (Climate Dynamics, 2020)

Seasonal Palmer drought severity index reconstruction using tree-ring widths from multiple sites over the central-western Da Hinggan Mountains, China since 1825 AD - Ruoshi Liu; Yu Liu; Qiang Li; Huiming Song; Xuxiang Li; Changfeng Sun; Qiufang Cai; Yi Song (Climate Dynamics, 2019)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Influence of ENSO on frequency of wintertime fog days in Eastern China - Huaying Yu; Tim Li; Peng Liu (Climate Dynamics, 2019)

Temperature variability inferred from tree-ring records in Weichang region, China, and its teleconnection with large-scale climate forcing - Yanchao Wang; Yu Liu; Huifang Zhang; Hui Wang; Jingli Guo; Erliang Zhang; Jun Wang; Xiao Li (Climate Dynamics, 2019)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Tree-ring stable carbon isotope-based April–June relative humidity reconstruction since ad 1648 in Mt. Tianmu, China - Yu Liu; Weiyuan Ta; Qiang Li; Huiming Song; Changfeng Sun; Qiufang Cai; Han Liu; Lu Wang; Sile Hu; Junyan Sun; Wenbiao Zhang; Wenzhu Li (Climate Dynamics, 2018)

Tree-ring-width-based PDSI reconstruction for central Inner Mongolia, China over the past 333 years - Yu Liu; Xinjia Zhang; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Climate Dynamics, 2017)

Possible role of pre-monsoon sea surface warming in driving the summer monsoon onset over the Bay of Bengal - Kuiping Li; Yanliang Liu; Yang Yang; Zhi Li; Baochao Liu; Liang Xue; Weidong Yu (Climate Dynamics, 2016)

Strong modulations on the Bay of Bengal monsoon onset vortex by the first northward-propagating intra-seasonal oscillation - Kuiping Li; Zhi Li; Yang Yang; Baoqiang Xiang; Yanliang Liu; Weidong Yu (Climate Dynamics, 2016)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)